Menggagas Bisnis Islam dalam Perekonomian Modern - M. Nur Asnawi (UIN Maulana Malik Ibrahim Malang, 2003)
In today's global world, the economy appears as a commander. Many economic actors do various terosoban in developing the business world. Interestingly, at this time also, some Muslim economists are also aggressive to make breakthrough business alternatives called Islamic business is a business that is controlled by the normative values of Islamic teachings, both from the way of acquisition and the way pengdayagunaannya In view of Islam, in conducting business activities, although there are values of freedom, value of ownership, and similarity all there are boundaries and territories that have been determined. Fakhri (l995) said that Islamic businesses are controlled by the law of halal and haram, totally different from non-Islamic business. On the basis of secularism based on material values, non-Islamic business is not paying attention to halal and haram in realizing its business objectives. Dalam dunia global saat ini, ekonomi tampil seolah menjadi panglima. Banyak para pelaku ekonomi melakukan berbagai terosoban dalam mengembangkan dunia bisnis. Yang menarik, pada saat ini pula, beberapa ekonom muslim juga gencar melakukan terobosan bisnis altematif yang disebut bisnis Islam yaitu adalah bisnis yang dikendalikan oleh nilai-nilai normatif ajaran Islam, baik dari cara perolehannya maupun cara pendayagunaannya Dalam pandangan Islam, dalam melakukan aktivitas bisnisnya, walaupun ada nilai-nilai kebebasan, nilai kepemilikan, dan kesamaan semuanya itu ada batas dan wilayah yang sudah ditentukan. Fakhri (l995) mengatakan bahwa bisnis Islami yang dikendalikan oleh aturan halal dan haram, sama sekali beda dengan bisnis yang non islami. Dengan berlandaskan pada asas sekularisme yang bersendikan nilai-nilai material, bisnis non islami tidaklah memperhatikan halal dan haram dalam merealisasikan tujuan bisnisnya.